The Influence of Motivation and Social Media Toward Students English Achievement With Classroom Management as Moderating Variable - khudriyah khudriyah; Moh. Fahmy Almuwallid (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2024)
Classroom management as external factor for students to learn is important to do by all teachers besides the students motivation, social media as external factor also influence their leraning. This research aimed to know whether or not clasrrom management as moderator variable influence the sudets motivaton and social media towards English achievement. This research used quantitaive approach. In collecting data the researcher used questionnaire, and documentation. The data then analyzed using multiple regression. Based on the significance result, it showed that students motivation is able to effect the students English achievement The social media does not effect the students English achievement, classroom management is significance influence the students English achievement, but classroom management does not significantly moderate the influence of students motivation towards students' English learning achievement, and classroom management also does not moderate the effect of social media towards students' English learning achievement.